Factors influencing the nutritional status of primary school children in the estate sector - Nalaka, G.P.S.; Weerasena, U.M.; Ekanayake, E.A.; Maduwansha, N.A.N.J.; Diunugala, H.P. (University of Jaffna, 2018)
The real wealth of a nation is its people. The well-being of a nation is decided by the nutritional status of the people. Yet, one of the main concerns, the developing world faces is malnutrition. The prevalence of malnutrition is high among the estate children in Sri Lanka, therefore it is very much important to study the factors of malnutrition in the estate sector in order to initiate appropriate effective strategies to minimize the malnutrition status of children. Thus, this study was designed to determine the factors influencing the nutritional status of primary children in the estate sector with reference to the Nuwara Eliya Medical Officer Area (MOH). As the target population, estate primary school children of the Nuwara Eliya MOH were considered. A sample of 125 estate school children was selected by using the simple random sampling method. Interviews, direct observations and a structured questionnaire were used to collect data. Data were presented by using descriptive statistical tools. Binary logistic regression models were applied to identify the factors associated with nutritional status. 40.45%, 38.57% and 25.7% of school children were suffering from underweight, stunting and wasting respectively. Gender, low birth weight, parent’s occupation, childhood diseases, food habits and parent’s awareness significantly influence the underweight. Gender, father’s height, family income and food habits significantly influence the stunting. Low birth weight, father’s education and occupation, father’s BMI, mother’s occupation, water source, childhood diseases, maternity diseases, healthy behavior, school influence and parent’s awareness significantly influence the wasting. The only factor that affects all the three nutritional status is the age. The Government need to focus its attention more on this regard and should initiate more workshops and programs to make the parents aware of the health of the children. Schools can take the initiation and launch programs.
Keywords: Estate children; Stunting; Under weight; Wasting